DETECTION OF ESCHERICHIA COLI IN CHILDREN STOOL WITH DIARRHEA PATIENTS USING CULTURE AND POLYMERASE CHAIN REACTION METHOD - Lokita Purnamasari; Muh Nasrum Massi; Ahyar Ahmad (Nusantara Medical Science Journal, 2017)
ABSTRACT Introduction : Diarrheal diseases are  a serious issue on health in developing countries and the liquid cause’s morbidity and mortality in children that cause the diarrhea pathogenic bacte- ria including Escherichia coli.  This research aims to detect E. coli in stool diarrhea patient of the  child with culture method and  Polymerase Chain Reaction. Methods : This research is descriptive research design with cross-sectional approach. The sampling was collected from some public health centers namely Pampang, Barabarayya, Antang  Perumnas, Tamangapa public health centers. Specimen testing process was conducted at Microbiology laboratory of the Teaching Hospital University of Hasanuddin to identify E. coli bacterium with the culture and  to detect eae gene and bfp with PCR technique. Results : The results indicate that from50 samples, there  are  15 samples (30%) of samples positively detection E. coli using culture method and  PCR  test using eae and  bfp primer found 20 (40%) and  1 sample (2%) positive enteropathogen E. coli. Conclusion : PCR  methods indicated the  result of E. coli bacteria results faster and more accurate that other  culture methods. Keywords : Diarrhea, Escherichia coli, Polymerase Chain Reaction